Evaluasi Kinerja Keuangan PT Bukalapak Tbk (BUKA) 2021-2024 - Titah Sari Nur Khassanah; Fany Lathifatul Nur Qori’ah; Abdul Jalil Abshor; Edi Supriyanto (Universitas Ratu Samban, 2026)
. This study aims to analyze the financial performance of PT Bukalapak Tbk during the 2021–2024 period using a financial ratio approach, including liquidity, solvency, activity, and profitability ratios. The research employs a descriptive quantitative method using secondary data in the form of PT Bukalapak Tbk’s annual financial statements obtained from the Indonesia Stock Exchange. The analysis is conducted by calculating and interpreting financial ratios to assess trends and the company’s financial condition over time. The results indicate that PT Bukalapak Tbk has a high level of liquidity and a relatively conservative capital structure, as reflected by low solvency ratios. However, the activity and profitability ratios demonstrate suboptimal performance, characterized by low asset utilization efficiency and limited rates of return. These findings suggest that although the company is in a financially stable position in terms of liquidity and solvency, improving operational efficiency and profitability remains the main challenge.